The genome sequence of the Red-clover Case-bearer, Coleophora deauratella Zeller, 1846 [version 1; peer review: 2 approved] - Denise C. Wawman; Liam M. Crowley (Wellcome Open Research)
We present a genome assembly from an individual female Coleophora deauratella (the Red-clover Case-bearer; Arthropoda; Insecta; Lepidoptera; Coleophoridae). The genome sequence is 518.4 megabases in span. Most of the assembly is scaffolded into 31 chromosomal pseudomolecules, including the Z and W sex chromosomes. The mitochondrial genome has also been assembled and is 15.76 kilobases in length.